Optimization of encapsulation of natural dye by cyclodextrin using response surface methodology - Nor Ashikin, Abdul Hamid (2010)
Nowadays,cyclodextrin widely used in industries due to its ability in encapsulation process with natural dye. However, the production cost for cyclodextrin is very expensive.A study on how to reduce the production cost by optimization of pH, concentration of cyclodextrin and temperature effect on encapsulation of natural dye by cyclodextrin using Response Surface Methodology(RSM)was successfully done. During the preliminary experiment,one factor at a time was employed to screen the best range for pH,concentration of cyclodextrin and temperature.All the parameter ranges obtained were used in RSM.RSM software in Design Expert version 6.0.8 was used with Central Composite Design(CCD) mode.Seventeen sets of experiments with different parameter values were suggested by the software.The predicted optimum values for pH,concentration of cyclodextrin,temperature and concentration of encapsulation of natural dye-β-cyclodextrin were pH 3.11,0.004 mol/L,60 oC and 1.27763 g/L respectively.One set of experiment was run using the optimized parameter and as a result,1.2534 g/L concentration on encapsulation of natural dye-β-cyclodextrin was recorded. Before optimization, concentration on encapsulation of natural dye-β-cyclodextrin was only 0.775 g/L and the concentration was increased by 38.17% after optimization. The optimization also reduces the cost and energy consumption as the pH reduced from pH 10.5 to pH 3.11, concentration of cyclodextrin reduced from 0.005 mol/L to 0.004 mol/L and temperature was reduced from 70 oC to 60 oC. As a conclusion, this study was successful to increase encapsulation of natural dye by cyclodextrin production, reduce the energy consumption and also be able to reduce the production cost of cyclodextrin.